Changes in the Territorial and Administrative Division of Northwest Russia over the Soviet Period - Manakov, Andrey G.; Mikhaylova, Anna A. (International Journal of Economics and Financial Issues, 2015)
The principles of internal territorial and administrative division are a staple of Russia’s statehood. The paper deals with the analysis of changes made to the territorial and administrative divisions of Northwest Russia over the Soviet period (1917-1991), mainly in upper-level units (gubernia, oblast, krai, and republic), and partly at the medium level, such as ouezd and okrug. The analysis presented here is heavily based on cartographic materials. The paper gives an overview of the large-scale administrative reforms of the Soviet period and determines the periods of stability and instability of administrative boundaries within the current territory of Northwest Russia. According to the analysis of the alterations in territorial and administrative divisions made during the Soviet period, within three decades after the 1927 enlargement reform the network of the upper-level units began to mirror those of pre-revolutionary time. Since 1957, the system of territorial and administrative divisions has been relatively balanced, with no significant changes made to it up to the present day. The results of this research will be used to construct the models of historical periodization and changes in the geography of Northwest Russia. Keywords: territorial and administrative units, Soviet period, Northwest Russia JEL Classifications: N9; P2; R00